Degradation of vitamin C in a product made from mango (Mangifera indica L.) and whey protein (2017)
This study aimed to determine the kinetics of vitamin C degradation in a product made from mango pulp (Mangifera indica L.) and whey protein powder, in order to determine the effect of temperature on its conservation and further evaluate the behavior of the L*, a*, b* and the total color difference (ΔE) in the powder product. Vitamin C was determined by the aoac 967.21/90 method using 2,6-dichlorophenol indophenol, and the color was quantified with a HunterLab Color Flex EZ colorimeter. Vitamin C showed greater stability in the powder product stored at 4 °C with a concentration at the end of the eighth sampling week of 13.94 ± 1.2 mg/10 0 g-1 sample and showing a first order degradation kinetics with k1 values of 0.014 and 0.041 mg/100 g/week at temperatures of 4 °C and 28 °C, respec-tively. The greatest variations in color occurred in samples stored at 28 °C, indicating the influence of the temperature change on the product compo-nents. In addition, L*, a* and b* parameters were less affected under storage temperature of 4 °C, and their values correspond to a second degree polynomial.